Are human induced pluripotent stem cell derived cardiomyocytes a good cellular model for studying incomplete penetrance in arrhythmogenic cardiomyopathy?. (10th June 2022) - De Bortoli, M; Meraviglia, V; Mackova, K; Volani, C; Frommelt, LS; Schlittler, M; Cattelan, G; Konig, E; Rauhe, W; Barbuti, A; Zacchigna, S; Pramstaller, PP; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Regional Development Fund and Interreg V-A Italy-Austria 2014-2020 and Department of Innovation, Research and University of the Autonomous Province of Bolzano-South Tyrol (Italy). Background: Human induced pluripotent stem cell derived cardiomyocytes (hiPSC-CMs) were previously used to model several inherited heart diseases (1). Among these, arrhythmogenic cardiomyopathy (ACM) is characterized by a fibrofatty myocardial replacement and severe ventricular arrhythmias (2). ACM is mainly caused by mutations affecting proteins of intercalated discs (3) and shows incomplete penetrance and variable expressivity (4). Purpose: To evaluate whether hiPSC-CMs provide a good in vitro model to study incomplete penetrance in ACM. Material and methods: hiPSCs were generated from buffy coats of 6 close relatives. Three of them were ACM patients carrying a deletion of exon 4 in the PKP2 gene causing a premature stop codon, 2 were asymptomatic (ASY) PKP2 mutation carriers and 1 was a healthy control (CTR). Whole exome sequencing of the 6 individuals was performed. The purified hiPSC-CMs were cultured in basal and adipogenic medium and examined by ddPCR, western blot, Wes™ immunoassay system, patch clamp and immunofluorescence. Results: All family members tested negative for additional mutations in ACM genes. As expected, half the amount of wild type (wt) PKP2 mRNA was found in ACM and ASY than in CTR hiPSC-CMs (2.25±0.27vs4.29±0.70 wtPKP2/HPRT1; p=0.028) (2.08±0.38vs4.29±0.70 wtPKP2/HPRT1; p=0.052). Of note, the mutated (mut) PKP2 mRNA was detected and significantly more expressed in ACM than in ASY hiPSC-CMs (0.33±0.04vs0.11±0.06 mutPKP2/HPRT1; p=0.029). While we confirmed a reduced amount of wt plakophillin-2 protein in ACM and ASY compared to CTR hiPSC-CMs (0.19±0.07vs0.81±0.28 wtPKP2/GAPDH; p=0.016), (0.25±0.07vs0.81±0.28 wtPKP2/GAPDH; p=0.11), the truncated protein was not detected. Moreover, a significantly lower expression of the active form of β-catenin (ABC) has been shown in ACM and ASY than in CTR hiPSC-CMs (0.93±0.18vs1.30±0.09 ABC/GAPDH; p=0.057), (0.76±0.10vs1.30±0.09 ABC/GAPDH; p=0.0057). In basal medium, ACM hiPSC-CMs had a significant lower overall sodium current density compared to CTR (-49.82±2.8 vs -69.38±4.8 pA/pF; p<0.0001) and to ASY (-49.82±2.8 vs -68.92±4.3 pA/pF; p<0.0001) hiPSC-CMs. In adipogenic medium, ACM hiPSC-CMs showed a higher lipid accumulation and a higher sarcomere disorganization than CTR (1580±219vs615±199 intensity/nuclei; p=0.0351) (0.019±0.001vs0.028±0.003 myofibril alignment index; p=0.039) and ASY (1580±219vs689±146 intensity/nuclei; p=0.0059) (0.019±0.001vs0.027±0.001 myofibril alignment index; p=0.010) hiPSC-CMs. Conclusions: Here we report that ACM express a significantly higher amount of mutated PKP2 mRNA than ASY iPSC-CMs. Even though no differences were detected for plakophilin-2 and active β-catenin proteins between ACM and ASY iPSCM-CMs, the ACM showed a fatty phenotype and altered electrical activity that differed significantly from the CTR as well as from the ASY hiPSC-CMs, demonstrating that these cells provide a valid model to study incomplete penetrance in ACM.